Definitions of palaeo-coasts in relation to beachrocks with the application of digital technologies. The case study of Romanos beach, Pylos - Μπηλίτση, Ευαγγελία (Πανεπιστήμιο Πελοποννήσου, 2022)
The last steps of the sciences are accompanied by the collaboration of scientists of different disciplines and a great contribution of new technologies. This paper presents the way in which palaeocoasts are measured and calculated in relation to the formations of beachrocks found along them. The purpose of the work is to highlight the way in which the application of digital technologies contributes to research and more specifically with the use of an unmanned UAV (drone). The application of the aforementioned concerns the beach of Romanos in Pylos, on the beach where the Western Resort of the Costa Navarino complex is located today. Given the importance of photogrammetry and the new technologies that are often associated with it, the specific coast was mapped and entered into the GIS program. In conclusion, based on the findings of the area during the field research (many different sediments and marine shell (fossils) and what was observed after the processing of the impression images, the formations of beachrocks arose from the old coast, in the place of which there is now the new coast with today's data. From the above data arise new questions and perspectives for new research related to the dating of the rocks of the formations through sediments and the calculation of the position of the old coast, as well as the change of the water level in the specific area.
Ορισμοί παλαιοακτών σε σχέση με απολιθωμένες ακτογραμμές με την εφαρμογή ψηφιακών τεχνολογιών. Η μελέτη περίπτωσης της παραλίας του Ρωμανού στην Πύλο
Keywords: Παράκτια αρχαιολογία -- Ελλάδα -- Μεθοδολογία; Αρχαιολογική έρευνα -- Ελλάδα --Μεσσηνία -- Πύλος; Πετρώματα -- Ελλάδα --Μεσσηνία -- Πύλος; Απολιθώματα -- Ελλάδα --Μεσσηνία -- Πύλος; Παραλία Ρωμανός (Πύλος, Ελλάδα) -- Αρχαιότητες; Αρχαιολογία -- Μεθοδολογία; Αρχαιολογία -- Τεχνολογικές καινοτομίες -- Ελλάδα -- Μεσσηνία -- Πύλος; Shorelines; Beachrocks; Digital technologies; Palaeocoasts; Photogrammetry; Remote sensing systems; UAV; 3D model; GIS; Dating; Luminescence; Ακτογραμμές; Ιζηματογενή πετρώματα; Ψηφιακές τεχνολογίες; Παλαιοακτές; Φωτογραμμετρία; Συστήματα τηλεπισκόπησης; Μη επανδρωμένο εναέριο όχημα; Μοντέλο τριών διαστάσεων; Γεωγραφικό σύστημα πληροφοριών; Χρονολόγηση; Φωταύγεια